Impact analysis of beef cattle agribusiness on income: A double difference approach (Journal of the Bangladesh Agricultural University, 2016)
This study examined the impact on income of small-scale beef cattle enterprise in Pabna and Sirajganj districts. Data were obtained from 180 cattle fattening participant farmers and 180 non participant farmers from two areas in January and December 2014. Data were collected through the use of structured survey schedules and analyzed by the use of descriptive statistical tools such as means and percentages and also paired t-statistics and chow test were used for the data analysis The Double-Difference (DD) estimator is used to estimate changes in income from before to after benefiting from beef cattle agribusiness between participant farmers and non-participant farmers. Result shows that the net farm income of beef cattle agribusiness entrepreneur increases from BDT 6791.17 before participant to BDT 10289.65 after participant of cattle fattening. There was also an increase in the net farm income of the non-participant farmers from BDT 6750.01to BDT 8437.51during beef cattle agribusiness study. On the average, the net farm income of participant farmers increased by 51.52% and non-participant increased by only 25.0%. The mean increased income was significantly different between participants and non-participant farmers of beef cattle fattening at 10% level of significance. Chow test analysis showed a significant change between the coefficients and intercept of the respondents income implying that beef cattle agribusiness contributed positively to the increased income realized by the farmers over that of non-farmers. Hence, it can be conducted that beef cattle agribusiness has positive impact on income of the farmers. The study recommends intensive support services from government and non government institutions to improve the performance of the beef cattle agribusiness.J. Bangladesh Agril. Univ. 13(1): 109-115, June 2015